FKM torsion test machine (A student model) / Azrol Hisham Abdullah - Abdullah, Azrol Hisham (Faculty of Mechanical Engineering, 2003)
Engineering training involves classroom-learning, lab works, and industrial training. These elements are essential for preparing engineering graduates when entering into professional areas. Most of the time, a subject is taught with greater emphasis on the theoretical viewpoint rather than practical aspect. However students are exposed on experimental works to relate the theoretical concept to the technical work. It is known that studies become more effective with the aid of practical applications and experimental works. As a result, a fresh engineering graduate, on entering the job-market would gain some amount of practical knowledge. With this in mind, an attempt has been made to design a testing apparatus that is useful for engineering students. Students can utilize this work project to perform a series of torsion testing using the modified design torsion test machine.